Towards a Jewish-Christian-Muslim theology - Burrell, David B. (Chichester, West Sussex : Wiley-Blackwell, 2011)
'Towards a Jewish-Christian-Muslim Theology delineates the ways that Christianity, Islam, and the Jewish tradition have moved towards each another over the centuries and points to new pathways for contemporary theological work. Explores the development of the three Abrahamic traditions, brilliantly showing the way in which they have struggled with similar issues over the centuries. Shows how the approach of each tradition can be used comparatively by the other traditions to illuminate and develop their own thinking. Written by a renowned writer in philosophical theology, widely acclaimed for his comparative thinking on Jewish and Islamic theology. A very timely book which moves forward the discussion at a period of intense inter-religious dialogue'--
'Religious debate among Jewish, Christian, and Islamic scholars has acquired urgent new dimensions in recent years. Yet over the course of 1400 years, what have the Abrahamic traditions really learned from each other? Brilliantly demonstrating the ways that Christianity, Islam, and the Judaism have struggled with similarly intractable issues over the centuries, Towards a Jewish-Christian-Muslim Theology offers insightful new pathways for productive theological work, along with deep insights into the topic of faith itself. Burrell uses exercises in'creative hermeneutics' to show how each tradition struggles with complex issues, and how comparative inquiry illuminates those issues to the benefit of each tradition. For each key topic explored, renowned religious scholar and theologian David B. Burrell shows how intellectual trends of their day may be read to extend the reach of each tradition itself. By illuminating the actual and potential interaction among the dominant monotheistic religions, Towards a Jewish-Christian-Muslim Theology offers inspiration for continued theological dialogue and hope for people of all faiths in the 21st century'--
Includes bibliographical references and index.
Keywords: Religions -- Relations; Abrahamic religions; Theology